Production of B4C Reinforced Composite Materials and Investigation of Their Bending Strength - Yılmaz Mutlu; Halit Doğan (Journal of Advanced Research in Natural and Applied Sciences)
In this study, AA2024 aluminum alloy was selected as the matrix material, while B4C was selected as the reinforcement material, and particle-reinforced Al-matrix composite materials were produced using the powder metallurgy method. Examinations were made to determine the effects of different reinforcement particle ratios and sintering temperatures on the mechanical properties of the AA2024 matrix composite materials that were produced. The powders were compressed in a metal mold at room temperature and a pressure of 525 MPa under a uniaxial press. The raw specimens that were obtained were sintered for 45 minutes at different temperatures. The produced composite materials were subjected to three-point bending tests and hardness measurements. Optical microscopy analysis was carried out for characterization. The results allowed us to draw a conclusion on how the reinforcement material in the produced specimens affected Al-matrix composite properties. It was determined that the B4C reinforcement added to the matrix increased the hardness values of the composites at all sintering temperatures, the highest bending strength was obtained in the composite with 10% B4C particle reinforcement, and in general, the B4C reinforcement was homogeneously dispersed in the matrix. Increased B4C reinforcement ratios resulted in higher hardness values in the composite materials.